El lenguaje poético de Marie-Célie Agnant - Cremades Cano, Isaac David (Anales de Filología Francesa, 2009)
Le livre d’Emma, of the Haitian authoress Marie-Célie Agnant, introduces us to a rich world full of images of nature, through an expressive poetical language worthy of study. With a great evocative power, the colors blue, red, the smells and the natural phenomena rescue from the memory of the black women a past of loneliness, racism and exclusion that has marked their particular condition: la malédiction des négresses. This original writing style joined to an unique sensibility, enable her to express her creativity and sensibility in her book of poems Balafres. Thanks to which we can reassert an original and recurrent style who allows us to analyze the poetical language of the authoress.